MOTIF DAN DAMPAK PERNIKAHAN DINI DI INDARUNG NGALAU BATU GADANG - Murisal Murisal (IAIN Batusangkar, 2017)
Motif and Impact of Early Marriage in Indarung Ngalau Batu Gadang.Penelitian is motivated by teenagers who married early on. Today, young men and women have a tendency to be less prepared to enter the home life, they are only ready to marry (ready here can be interpreted, maturity in terms of financial, understand what the meaning of marriage according to marriage law) is the bond of inner birth between a man and a woman as husband and wife for the purpose of forming a happy and eternal family (household) based on the Supreme Godhead while they are not ready to set up a home, whereas to build a household requires preparation both physically and spiritually . The purpose of this study to determine the motives underlying adolescents to make early marriage and the impact caused in the household as a result of the marriage.